Assessment Frameworks Utilized by PIAAC for Evaluating Adult Problem-Solving Skills - Zulkardi; Ratu Ilma Indra Putri; Ahmad Fauzan; Rizha Alfajri; Sary Silvhiany; Viona Adelia; Yentri Anggeraini; Dhea Anisah Putri; Niken Wahyu Utami; Nendra Mursetya Somasih Dwipa; Rahma Siska Utari; Yovika Sukma; Dea Alvionita Azka; Rafki Nasuha Ismail; Novita Sari; Aqilul Asra; Nadya Fitriani; Laela Sagita (Mathematics Education Journal, 2026)
This study explores the assessment framework used in the Programme for the International Assessment of Adult Competencies (PIAAC) to evaluate adult problem-solving skills, focusing on its conceptual. In response to the increasing global demand for foundational and adaptive skills, PIAAC serves as a key international tool for measuring literacy, numeracy, and problem-solving in technology-rich environments. A systematic literature review (SLR) was conducted using PRISMA 2020 guidelines, analyzing 27 Scopus-indexed studies published between 2015 and 2026. The methodological quality of these studies was evaluated using the Mixed Methods Appraisal Tool (MMAT). The findings indicate that the PIAAC framework conceptualizes adult competencies as multidimensional, functional, and context-dependent, extending beyond basic literacy and numeracy. These competencies are essential for effective problem-solving in real-life and digital contexts. The framework employs a comprehensive design that integrates cognitive skills, background variables, task features, and advanced analytical models to assess diverse populations. Moreover, the inclusion of technology-rich tasks and log file data highlights that competence emerges through dynamic interactions between individuals and their environments. Overall, PIAAC provides an integrative framework linking competencies, cognitive processes, and real-world outcomes.